ANALISIS KUALITAS PELAYANAN ADMINISTRASI TATA USAHA PADA SMK TARUNA BANGSATAHUN AJARAN 2024-2025 - Predianto Kusuma; Hamidah Darma; Maulana Akbar Sanjani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study seeks to analyze the quality of administrative services provided by the School Administration Office (Tata Usaha) at SMK Taruna Bangsa Sawit Seberang. Effective administrative services play a crucial role in ensuring the smooth operation of teaching and learning activities within the school. The research employs a descriptive qualitative approach, with data collected through observations, interviews, and documentation. Findings reveal that the administrative services at the institution are generally satisfactory. The administrative personnel demonstrate friendliness, responsiveness, and professionalism in carrying out their duties. Nonetheless, several challenges remain, including an insufficient number of staff members, limited office equipment, and a filing system that has not yet been fully optimized. At SMK Taruna Bangsa, some records are still managed manually, which makes document retrieval more time-consuming. Therefore, it is recommended that staff training, additional work facilities, and the adoption of a digital administrative system be implemented to enhance service speed and efficiency.